'Lords of the dance' as double agents: elite actors in and around the legal field. Issue 2 (8th June 2016) - Dezalay, Yves; Garth, Bryant G.
Abstract : This article starts from the useful image of professions as 'Lords of the Dance' playing central roles in constructing and managing institutions. Drawing on our own comparative research and Pierre Bourdieu's sociological approach, we present an alternative and in part complementary analysis of the presumed phenomenon. We suggest that a focus on professions generally, the legal profession, or the professional services firm as the unit of analysis neglects the key role of a relatively small group of double agents and brokers, typified by elite lawyers or jurists who combine forms of social, familial, learned, political and other capital with stature within the profession. These individuals broker institutional change in part through their professional stature but also on behalf of themselves and the interests that they represent. The model comes from law but can be found also with other groups, including a small number of investment bankers and business consultants. The article explores the genesis of this role through the interaction between legal fields and fields of state power in Europe, the role of the elite double agent in brokering change, and how it has evolved to privilege especially a relatively small number of professors in Germany, barristers in Great Britain, and French advocates—in each context acting both inside the law but also above, below, and around through their connections to other social groups. The conclusion of the article seeks both to contrast the approach taken in this article to the literature on professions and organizations, and to suggest how this approach can be used also to examine the processes of US-led globalization, where the counterpart elite jurist is the corporate lawyer statesperson.